Sprayable Biodegradable Polyester-Urethane-Urea Mulching Treatment Increases Abundance of Soil Microbes - Cuyler K. Borrowman; Raju Adhikari; Kei Saito; Karen Little; Stuart Gordon; Antonio F. Patti (Agriculture)
The paper investigates for the first time the impact of a novel sprayable, biodegradable polyester-urethane-urea (PEUU) mulch on the microbial community composition of an agricultural soil. In this study changes to the composition of the soil microbial community and in soil enzyme activity involved in nutrient cycling were monitored on tomato plants grown under controlled greenhouse conditions. Particular attention was given to impacts on the relative changes in abundance of soil microbes. The PEUU mulch reduced the abundance of a small number of soil microbe taxa, but also provided an environment in which some taxa, which were comparatively rare in initial and unmulched soils, thrived. Importantly, the relative abundances of Azospirillum, Noviherbaspirillum, Exophiala, Phoma, Chaetomium and Clonostachys species all increased in soils treated with PEUU mulch. Principal coordinates analysis revealed the microbial community composition on PEUU films alone and in PEUU treated soil were most similar, while the PEUU films’ microbial community differed the most from the initial soil’s microbial community. These results indicate that from an agricultural productivity and an environmental safety standpoint the use of PEUU mulch may be preferable to PE and could provide additional plant growth benefits by increasing the abundance of soil microbes.